The economics of taxing net wealth: A survey of the issues - Jan Schnellenbach (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2012)
This paper surveys possible motivations for having a net wealth tax. After giving a short overview over the state of wealth taxation in OECD countries, we discuss both popular arguments for such a tax, as well as economic arguments. It is argued that classical normative principles of taxation known from public economics cannot give a sound justification for a net wealth tax. The efficiency-related effects are also discussed and shown to be theoretically ambiguous, while empirical evidence hints at a negative effect on GDP growth. Finally, it is argued that despite of widespread and persistent lobbying for a revitalization of the net wealth tax, this is unlikely to happen due to political economy constraints.
Keywords: H24; D31; H23; H21; H22; 330; net wealth tax; wealth; inequality; redistribution